1987
DOI: 10.1530/acta.0.1150119
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an androgen receptor in porcine Leydig cells

Abstract: Cytosol and nuclear androgen receptor concentrations were measured in freshly prepared and cultured Leydig cells of immature pig testis with exchange assays using [3H]methyltrienolone as labelled ligand. Androgen receptors in Leydig cells had high affinity for [3H]methyltrienolone and steroid binding specificity typical of an androgen receptor. The mean receptor concentrations were 76 fmol/mg protein and 210 fmol/mg DNA for cytosol and nuclei, respectively. In sucrose gradients, cytosol androgen receptors sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…1979, Ekman et at. 1982, Isomaa et al 1987, Muechler 1987. In our study, RBAs to bovine uterine ARC are similar to those reported above in various mammalian tissues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1979, Ekman et at. 1982, Isomaa et al 1987, Muechler 1987. In our study, RBAs to bovine uterine ARC are similar to those reported above in various mammalian tissues.…”
Section: Discussionsupporting
confidence: 90%
“…5a-DHT bound with higher affinity to ARC than did testosterone in bovine and human uterine tissue (de Boer et al 1986, Muechler 1987, in rat (Gaubert et al 1980) and human prostatic cytosol (Ekman et at. 1982) but not in porcine Ley dig cells (Isomaa et at. 1987).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation